PENGEMBANGAN MODEL TEAM ASSISTED INDIVIDUALIZATION PADA MATERI OPERASI HITUNG BILANGAN BULAT DI KELAS V SD - Wilmintjie Mataheru (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: The study was intended to develop a teaching and learning set of Team Assisted Individualized on the materials of integer arithmetic operation. The development processes were define, design, and develop. The subjects of the study were the fifth graders of Public Elementary School 2 Later. The data was collected from the expert validation, observation, questionnaire, and the students’ achievement test. The study produced a teaching and learning set which included (1) lesson plan, (2) students’ book, and (3) students’ worksheet. The validator gave 3.6 for the teaching and learning set; 84.6% for the implementation of the teachers’ activities; 86.4% for the implementation of the students’ activities; 93.1% for the teachers’ respond; 92.5% for the students’ respond l and 19 out of 21 students who took the achievement test achieved 90.5% of the completeness.Keywords: team assisted individualized, arithmetic operation, integer.Abstrak: Penelitian ini bertujuan mengembangkan perangkat pembelajaran model Team Assisted Individualized pada materi operasi hitung bilangan bulat. Proses pengembangan ditempuh melalui define, design, dan develop. Subjek penelitian siswa kelas V SD Negeri 2 Lateri. Pengumpulan data menggunakan validasi ahli, observasi, angket, dan tes hasil belajar. Penelitian ini menghasilkan perangkat pembelajaran berupa (1) Rencana Pelaksanaan Pembelajaran (RPP), (2) Buku Siswa (BS), dan (3) Lembar Kerja Siswa (LKS). Validator memberikan skor 3,6 untuk perangkat pembelajaran; keterlaksanaan aktivitas guru 84,6%; keterlaksanaan aktivitas siswa 83,1%; respons guru 93,1%; respons siswa 92,5%; dan 19 dari 21 siswa yang mengikuti tes hasil belajar mencapai ketuntasan 90,5%.Kata kunci: team assisted individualized, operasi hitung, bilangan bulat.